Incidence and Prevalence of celiac disease in Hazara Division, KP Pakistan by anti-tissue transglutaminase antibody as diagnostic tool - Abdul Haseeb, Azam Hayat, Aamer Ali Khattak, Mujaddadur Rehman, Faheem Jan, Bilal Ahmed, Usman Ayub, Rizwan Ullah, Shafiquer Rehman, Anum Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To check the prevalence of CD among different age groups and across gender in population of Hazara division and to determine the distribution of CD through ELISA technique. Study design: A cross sectional study was designed at department of medical Lab Technology, University of Haripur, Haripur (KPK). Place and duration: Samples were analyzed at Hamdard laboratory from November 2016 to May 2017. Methods: we used ELISA technique in our study. According to the company instructions, the ELISA method was used to detect anti-tissue transglutaminase antibodies using this approach, which is sensitive, and specific. We target anti-tissue transglutaminase antibody by this technique which is an optimistic antibody assisting in the validation of the CD diagnostic test. Results Total 8000 patients samples were collected from Gastro OPD of district head quarter (DHQ) hospital Haripur, Abbottabad and Mansehra of Hazara Division. Out of 8000 the 6880(86%) male and 1120(14%) females. About 568(7.1%) cases were highly positive while 120(1.5%) cases were weak positive and the rest of 7312 (91.4%) cases were negative. Out of 568(7.1%) highly positive cases 452(79.6%) were males and 116 (20.4 %) were females. Furthermore 120(1.5%) of weak positive cases 74 (61.7%) were males and around 46(38.3%) were female. Conclusion: For centuries, CD has indeed been kept under wraps, with little to no known about what is a comparatively common health problem. This is only recently that we have improved our knowledge of its Prevalence, pervasiveness, prognosis, and pathophysiology that has assisted in the creation of new CD treatment strategies. Key words: Celiac disease, ELISA, Anti-tissue transglutaminase, Gluten.